Efficacy of Different Irrigant Activation Systems on Debris and Smear Layer Removal: A Scanning Electron Microscopy Evaluation - Ronald Wigler; Moran Herteanu; Yuval Wilchfort; Anda Kfir (International Journal of Dentistry)
Background. Irrigation is an essential component of root canal treatment to enable cleaning beyond the reach of mechanical instruments. The study aimed to assess and compare the efficacy of different final irrigation protocols, including sonic- and ultrasonic-powered irrigant-activation systems, on debris and smear layer removal in the coronal, middle, and apical thirds of straight oval root canals. Materials and Methods. Straight oval root canals of 60 human mandibular incisors were prepared to size 40.04 and divided into four groups (n = 15) according to the final irrigation protocols: (a) Eddy sonic activation (b) endosonic passive ultrasonic irrigation (PUI), (c) irrisafe PUI, and (d) manual syringe and needle irrigation with no additional activation, which served as control. After the treatment procedures, the roots were split and observed using scanning electron microscopy. The presence of remaining debris and smear layer at the coronal, mid-root, and apical thirds of the canals were evaluated using a score system and statistically analyzed using multinominal models with significance level set at p<0.05. Results. None of the final irrigation protocols completely removed all debris and smear layer from all root canals. When the syringe and needle were used without activation, more debris and smear layer were found in the apical third of the canals. Activation of the final irrigant with each of the three devices significantly reduced the presence of debris in the apical third, compared to the syringe and needle final irrigation, with no difference among the three activation devices. Eddy and irrisafe activation also significantly reduced the residual smear layer in the apical third, compared to syringe and needle alone, while the reduction in the remaining smear layer by endosonic activation did not reach the significance level. Conclusions. Removal of debris and smear layer from the apical part of the root canal by syringe and needle irrigation alone may be significantly improved by using sonic or ultrasonic activation of the final irrigant. Endosonic activation was less effective in removal of smear layer from the apical part of the canals compared to the other two activation systems.